Development of a bioactive chitosan HPMC-based membrane with tea polyphenols encapsulated in β-cyclodextrin as an effective enhancement. (June 2021) - Song, Jinxing; Feng, Huafeng; Wu, Mengqi; Chen, Linxiao; Xia, Wei; Zhang, Wenqing
Graphical abstract: Highlights: A novel biodegradable membrane of chitosan/HPMC containing polyphenols encapsulated composite was obtained and characterized. β -Cyclodextrin and tea polyphenols were proved for good encapsulation and the composite was firstly added chitosan/HPMC film. β -Cyclodextrin improves compatibility of polyphenols and HPMC and the composite was well characterized. The membrane with good mechanical performance presented obviously increased antibacterial activities. Abstract: Biodegradable membranes of chitosan and its composite with other natural polymers provide a promising solution for biomaterials. To further improve the antibacterial activities of chitosan (CS)/hydroxypropyl methyl cellulose (HPMC) membrane, natural extracts tea polyphenols (TP) were employed in this work. And TP was encapsulated by β -cyclodextrin (CD) beforehand to improve its compatibility with HPMC. To our knowledge, it's the first time ever reported to use CD encapsulated TP in CS/HPMC membranes. And variety characterization results such as Fourier transform infrared spectroscopy (FTIR), ultraviolet spectra (UV) and dynamic light scattering (DLS) showed that TP had successfully encapsulated with CD. After the solvent blending of CS/HPMC and CDTP, CS/HPMC/CDTP membrane was prepared by a casting method and exhibited good toughness and tensile strength. Finally, bacterial inhibitive rate and inhibition zones of the membrane with E. coli and S. aureus proved the enhanced antibacterial as expected. And the morphology of the bacteria was observed to estimate the possible interaction approach of materials and bacteria. The novel biodegradable membrane can be used for antibacterial coating application.